Sub‐cellular imaging shows reduced photosynthetic carbon and increased nitrogen assimilation by the non‐native endosymbiont Durusdinium trenchii in the model cnidarian Aiptasia. (21st July 2020) - Sproles, Ashley E.; Oakley, Clinton A.; Krueger, Thomas; Grossman, Arthur R.; Weis, Virginia M.; Meibom, Anders; Davy, Simon K.
Summary: Hosting different symbiont species can affect inter‐partner nutritional fluxes within the cnidarian–dinoflagellate symbiosis. Using nanoscale secondary ion mass spectrometry (NanoSIMS), we measured the spatial incorporation of photosynthetically fixed 13 C and heterotrophically derived 15 N into host and symbiont cells of the model symbiotic cnidarian Aiptasia ( Exaiptasia pallida ) when colonized with its native symbiont Breviolum minutum or the non‐native Durusdinium trenchii . Breviolum minutum exhibited high photosynthetic carbon assimilation per cell and translocation to host tissue throughout symbiosis establishment, whereas D. trenchii assimilated significantly less carbon, but obtained more host nitrogen. These findings suggest that D. trenchii has less potential to provide photosynthetically fixed carbon to the host despite obtaining considerable amounts of heterotrophically derived nitrogen. These sub‐cellular events help explain previous observations that demonstrate differential effects of D. trenchii compared to B. minutum on the host transcriptome, proteome, metabolome and host growth and asexual reproduction. Together, these differential effects suggest that the non‐native host–symbiont pairing is sub‐optimal with respect to the host's nutritional benefits under normal environmental conditions. This contributes to our understanding of the ways in which metabolic integration impacts the benefits of a symbiotic association, and the potential evolution of novel host–symbiont pairings.